OVERVIEW OF THE POTENTIAL OF TRADITIONAL MEDICINAL HERBS IN THE TREATMENT OF GASTRIC ULCER AND GASTROESOPHAGEAL REFLUX DISEASE (Vietnam Journal of Community Medicine, 2026)
Peptic ulcer disease (PUD) and gastroesophageal reflux disease (GERD) are common chronic gastrointestinal disorders that significantly impair the quality of life of millions of people worldwide. Although modern medical treatments, particularly proton pump inhibitors (PPIs), have demonstrated high efficacy, long-term use remains associated with concerns regarding adverse effects and drug resistance. In this context, Traditional Medicine, with its extensive pharmacopeia of medicinal herbs, offers a promising complementary and integrative therapeutic approach. This narrative review aims to provide an overview of the potential role of Vietnamese herbal medicines in the management of PUD and GERD. The herbal formula “Da Khoi Cot” is presented as a representative case study to illustrate the multi-target therapeutic principle of Traditional Medicine, combining agents with acid-neutralizing properties (Sepiae Os), mucosal protective effects (Ardisia silvestris leaves), anti-inflammatory activity (Oldenlandia diffusa), and gastrointestinal motility regulation (Aurantii Fructus Immaturus and Paeoniae Radix Alba). Preliminary evidence, primarily derived from preclinical studies (in vitro and animal models), has suggested these pharmacological activities. This review highlights the growing trend toward the development of standardized herbal preparations grounded in evidence-based medicine as a safe and effective adjunctive strategy in the comprehensive management of gastric disorders. However, it must be emphasized that current evidence is insufficient for these herbal therapies to replace standard modern medical treatments, particularly given the potential malignant transformation associated with PUD and GERD.